Characteristics of the Epidemic Situation Associated with Acute Respiratory Viral Infections in the Russian Federation during the Pandemic Spread of COVID-19 - T. A. Semenenko; V. G. Akimkin; E. I. Burtseva; A. V. Nozdracheva; E. G. Simonova; A. V. Tutelyan; S. V. Ugleva; S. N. Kuzin (Эпидемиология и вакцинопрофилактика, 2022)
Annualy, SARS occupy a leading position in terms of morbidity and the magnitude of the economic damage caused both in the world and in the Russian Federation. Currently, the most widespread pandemics are caused by the influenza A (H1N1) pdm09 virus and the new SARS-CoV-2 coronavirus, which occupy a common ecological niche and require studying the manifestations of the epidemic process of ARVI for further development of measures to improve epidemiological surveillance of this group of infections. Aim of the study was to investigate the current manifestations of the epidemic process of ARVI and influenza, including in the context of a new coronavirus infection (COVID–19) pandemic, on the territory of Russia and in Moscow. Materials and methods. The assessment of the long-term dynamics of the incidence of ARVI and influenza (from 1999 to 2021), as well as its age structure in the territory of the Russian Federation and in Moscow, was carried out. The main sources of information were: WHO: «The situation with COVID-19 in the European region», the domestic information portal Stopkoronavirus.rf, as well as data from Federal State Statistical Observation forms No. 2 and No. 6. Results. During the period 2013–2019, a strong positive correlation was revealed between the incidence rates of ARVI in the Russian Federation and Moscow (p = 0.8, with p < 0.05), which became negative with the spread of SARS-CoV-2: in the country, the incidence rate of ARVI increased by 11.5% in 2020 and 15.6% in 2021., in Moscow there was a decrease of 45.1% than the average in Russia, which could be due to the quality of differential diagnosis of ARVI and COVID-19. In 2021 the incidence rate of influenza decreased by more than 2 times in all Federal Districts of the country, with the exception of the capital region, where it became the maximum - 65.9 per 100 thousand population in 2021 (against 14.1 in 2019). In the age structure of influenza incidence, as well as ARVI, for the period from 2019 to 2021. the child population prevailed with the highest rates in the age groups of 1–2 years and 3–6 years. As the circulation of SARS-Cov-2 decreased to 15–19%, the activity of influenza viruses and other pathogens of the ARVI group increased (from 0.7–3.0% during the developed pandemic to 5.6–6.6% at the stage of its decline), which indicates a pronounced interference of pathogens detected at the global level in the system of Global Hospital Surveillance for flu. Conclusion. The forecast for the upcoming epidemic season 2022–2023 largely depends on the spread of the new coronavirus SARS-CoV-2, as well as its variability and the emergence of new variants. Nevertheless, there may be a significant increase in the incidence caused by the influenza A(H1N1)pdm09 virus, whose high activity was recorded in the current epidemic season in a number of countries in the Southern hemisphere.